AdriAtlas et IllyrAtlas, deux atlas informatisés de l’Antiquité romaine et du haut Moyen Âge - Francis Tassaux (Humanités Numériques)
AdriAtlas was made available on-line in November 2013. It is a geographic information system (GIS) developed for an ANR program with the purpose of including all sites located in the ancient Adriatic area, between the 11th century BCE and the middle of the 8th century CE. The database is populated by 19 research centers from Albania, Croatia, France, Italy and Slovenia, and is interlinked with AdriaZot, a collaborative Zotero bibliography. Since 2018 it has been extended with IllyrAtlas, a digitalised atlas of the Illyricum, the area between the Greek or hellenophone world and the Danube – for the High Roman Empire it includes the Dalmatian and Pannonian provinces and the part of Moesia which became Moesia Superior in 86, as well as the Noricum and the Rhaetia provinces. It is linked to the IllyriZot collaborative bibliography.The two atlases are multilingual, and available in open access to everyone. They are not only atlases and encyclopaedias, but also tools for research and publication.